Comparison of efficacy of the intermittent pneumatic compression with various pressures in reducing the primary lower extremity venous lymphedema of menopausal patients - Taradaj, Jakub; Halski, Tomasz; Ozon, Marcin; Rajfur, Joanna; Pasternok, Małgorzata; Kwaśna, Krystyna; Chmielewska, Daria; Piecha, Magdalena; Skrzypulec-Plinta, Violetta (Menopause Review/Przegląd Menopauzalny, 2013)
Introduction: The primary lymphedema and chronic venous insufficiency are important medical problems in women during menopause. Intermittent pneumatic compression has been accepted as a supplemental therapy for many years. However, due to the diversity of the clinical view of venous lymphedema and difficulties in the diagnosis, there is still no uniform and fully reliable treatment algorithm and international consensus. Aim of the study : To compare the efficacy of pneumatic compression of various pressure for the treatment of lower extremity venous lymphedema in menopausal patients. Material and methods: The study included 33 patients with chronic venous insufficiency and bilateral primary lymphedema of the lower limbs. Group A consisted of 10 patients aged from 46 to 56 years (mean age 51.2 years) who had used monthly therapy, treatments consisting of manual lymphatic drainage, multi-layer bandaging and intermittent pneumatic compression with a pressure of 120 mm Hg. Group B consisted of 10 patients aged from 45 to 58 years (mean age 53.3 years) who had identical basic treatment as group A, and intermittent pneumatic compression with a pressure of 60 mm Hg. Group C (control) consisted of 13 patients aged from 44 to 57 years (mean age 52.8 years) who were using only primary treatment without intermittent pneumatic compression. Results: It was found out that the greatest reduction in edema in patients undergoing compression settings with a pressure of 120 mm Hg. Comparison of the percentage reduction in edema showed a statistically significant advantage for group A to groups B and C, both for changes in the right (p = 0.01) and left limb (p = 0.01). Results in patients undergoing intermittent pneumatic compression with a lower pressure (60 mm Hg) were similar to those obtained in the control group. Conclusions: Intermittent pneumatic compression with a pressure of 120 mm Hg significantly helps to reduce the venous lymphedema in patients with menopause. It appears that the procedures with a pressure of 60 mm Hg are ineffective.